(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
As tidal energy nears commercial viability, the reliability and safety of a tidal energy device becomes more prevalent. A key aspect for determining their reliability and safety, along with reducing risk during operational deployment, is the structural integrity of tidal turbine blades. Therefore, a validated model for predicting the structural integrity of tidal turbine blades will aid in de-risking tidal energy technologies. In this study, a three-phase approach was used to formulate a strategy to predict the remaining fatigue life and residual strength of tidal turbine blades, over their operational lifespan. In Phase 1, the parameters influencing the structural properties of tidal turbine blades were identified based on the literature review, and the expertise in the field. Then, parameters were extensively studied and classified into four main impact groups, which include load conditions, design and manufacturing, degradation, and unexpected situations. Loading conditions on the blade are directly linked to hydrodynamic forces, maintenance, operating conditions, and corrosion effects. At the same time, these scenarios can vary with fluid-structure interactions, climate conditions, local site conditions, and maintenance and inspection schedules of the blades. The design and manufacturing category mainly represents the impact of the properties of composite materials, the geometry of the blade, and manufacturing process parameters. Similar to the other structures, tidal turbine blades are subject to deterioration and unexpected accidents during their service life, which significantly compromises the structural integrity of the blade. In Phase 2, a data management strategy was formulated related to identified four impact categories and investigated the possible methods of analysing the data. In this context, finite element analysis of composite tidal turbine blades was identified as the most appropriate tool to comprehensively examine collected data, prior to comparing the results to the field and laboratory-based test data. Mesh properties of the numerical models, test standards, instrumentation, and equipment used for field and laboratory-based structural testing of tidal turbine blades, as well as the accuracy of data acquisition systems, influence the comparison of these results. Finally, with the information gathered, as well as knowledge and experience in the field, a method for estimating the residual strength and remaining fatigue life of tidal turbines at each stage of their operation was formulated. The model will undergo a series of extensive validation processes using experimental testing datasets and will be used in the future to develop vulnerability curves related to the remaining structural life of the tidal turbine blades.